Well-being driven: The key entrepreneurial trait leads to the entrepreneurial success - Hassan, Mohamad Ghozali; Amjad, Tayyab; Mohd Sharif, Kamal Imran; Ismail, Mohd Azril; Kamantasha, Zakaria (2021)
This is an exemplary case of a successful entrepreneur named Zakaria who was driven by wellbeing of himself, his people and the society, which shows in his key decisions and actions while starting and running his entrepreneurial venture. He is mostly found driven towards societal well-being i.e., serving people with healthy food, rather than just materialistic gains, which has clearly led him to the entrepreneurial success. Out of many examples, in this case study, we chose to discuss his few major and most important well-being driven decisions and actions that gave him the ultimate edge in becoming successful. The key decisions include, entering into the niche of organic rice aiming to serve people with healthy food; spreading awareness about the benefits of consuming organic; working towards and achieving organic certification; uplifting the rural economy aiming at societal well-being; and not wasting natural resources aiming at environmental well-being. The case holds highly valuable learning for the entrepreneurship or business students who wish to start entrepreneurial careers after completing their degrees